Study Socioeconomic Level Citrus Growers In Panji Jaya Kapeh Kenagarian Talaok District of South Coastal District shadow - Saponggi, Saponggi; Drs. Dasrizal, MP, Drs. Dasrizal, MP (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aims to obtain data or information about the socio-economic level studies citrus growers in Kenagarian Kapeh Panji Jaya subdistrict shadow Talaok South Coastal District . This type of research is classified as descriptive research . The study population is a citrus farmer in Kenagarian Kapeh Panji Jaya subdistrict shadow Talaok South Coastal District . Samples were taken with a total sampling technique to sample amounted to 61 families . Data were collected by questionnaire guided , statistical analysis used is descriptive by using a percentage formula . The results showed that : 1 ) the educational attainment citrus farmers : many primary school , but also many who had not completed high school , 2 ) health condition of citrus growers are generally quite good , but in meeting the needs of health is still lacking , 3 ) Income levels of citrus farmers : source of income of the husband and wife , availability of sufficient food , penegeluaran average within 1 month of Rp 1,500,000 , 4 ) the state of the citrus farmers : the status of ones own home is a home , building semi- permanent condition 100 % , number of rooms 3 pieces , broad house building is less than 90 m and a source of home lighting on average of PLN.